EVIDENCE FOR A PROPOSED INITIATION COMPLEX FOR PROTEIN SYNTHESIS IN RETICULOCYTE POLYRIBOSOME PROFILES - Hoerz, Wolfram (1969)
Polysomes consisting of 40S ribosomal subunits attached to monosomes, disomes, trisomes, and tetrasomes have been isolated for the first time by the use of isokinetic sucrose density gradients. They are formed upon incubation of rabbit reticulocyte lysate in the presence of 10 mM NaF. It is proposed that these structures represent transient initiation complexes for protein synthesis.